From This Point Of View : 60 British Columbia painters, sculptors, photographers, graphic and video artists - Balkind, Alvin (Vancouver : Vancouver Art Gallery, 1977)
Blanck, Nora ; Burrows, Tom ; Cogswell, Barry ; Corsaut, Share ; Detheridge, Allan ; Dobereiner, John ; Falk, Gathie ; Green, Phyllis ; Hayward, Chris ; Kipling, Ann ; Kyooka, Roy ; Chien-Shih, Lin ; Lodge, Judith ; MacDonald, Murray ; McWilliams, Al ; etc.
From This Point Of View : 60 British Columbia painters, sculptors, photographers, graphic and video artists, Vancouver Art Gallery, Vancouver, September 7th to October 2nd, 1977
English
kunstcatalogus
Keywords: Canada; British Columbia